2011
DOI: 10.1073/pnas.1103877108
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of retinol dehydrogenase 10 in embryonic patterning and rescue of its loss of function by maternal retinaldehyde treatment

Abstract: Retinoic acid (RA), an active vitamin A metabolite, is a key signaling molecule in vertebrate embryos. Morphogenetic RA gradients are thought to be set up by tissue-specific actions of retinaldehyde dehydrogenases (RALDHs) and catabolizing enzymes. According to the species, two enzymatic pathways (β-carotene cleavage and retinol oxidation) generate retinaldehyde, the substrate of RALDHs. Placental species depend on maternal retinol transferred to the embryo. The retinol-to-retinaldehyde conversion was thought … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
134
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(142 citation statements)
references
References 53 publications
8
134
0
Order By: Relevance
“…Although Rdh1 expression increases 40-fold during embryogenesis, Rdh1-null mutants show no obvious signs of impaired development, but have abnormally high post-weaning adiposity (7). Rdh10-null mice, in contrast, die in midgestation with multiple, but not complete, dysfunctions in atRA-dependent processes (13,14,16,68). These two distinct phenotypes, along with different subcellular loci in the same cells, are consistent with the hypothesis that individual Rdh isoforms generate discrete pools of atRA to serve specific vitamin A-dependent functions.…”
Section: Discussionsupporting
confidence: 70%
“…Although Rdh1 expression increases 40-fold during embryogenesis, Rdh1-null mutants show no obvious signs of impaired development, but have abnormally high post-weaning adiposity (7). Rdh10-null mice, in contrast, die in midgestation with multiple, but not complete, dysfunctions in atRA-dependent processes (13,14,16,68). These two distinct phenotypes, along with different subcellular loci in the same cells, are consistent with the hypothesis that individual Rdh isoforms generate discrete pools of atRA to serve specific vitamin A-dependent functions.…”
Section: Discussionsupporting
confidence: 70%
“…However, the molecular patterning defects in RDH10-null mice do not refl ect a complete state of atRA defi ciency ( 45 ), suggesting that additional retinol dehydrogenases exist. RDH10 shares the highest sequence similarity with two other members of SDR16C family of proteins, RDHE2 (SDR16C5) and RDHE2S (SDR16C6) ( Table 1 and Fig.…”
Section: Biosynthesis Of Atra From Retinolmentioning
confidence: 99%
“…Others have reported that overexpression of human RDH10 in HepG2 cells induced a signifi cant antiproliferative response and upregulation of RAR ␤ ( 44 ), supporting the role of RDH10 in atRA biosynthesis. However, the ultimate proof came from recent mouse studies, which showed that inactivation of RDH10 function in mice either by mutations or a targeted gene knockout results in severe malformations and embryonic lethality due to insuffi cient production of atRA ( 41,45,46 ). This phenotype can be rescued by supplementation with atRA or all-trans -retinaldehyde ( 45,46 ).…”
Section: Biosynthesis Of Atra From Retinolmentioning
confidence: 99%
“…Indeed, previous rescue experiments in which RA was administered at different stages and doses confirmed the special sensitivity of proximal limb segments and Meis gene expression to RA availability (Niederreither et al, 2002). Regarding the Rdh10 analysis, while Rdh10-null mutants die around E10.5-E12.5, the model analyzed by Cunningham et al (Cunningham et al, 2013) is a hypomorph mutant called T-Rex, the lethal phase of which is E13.5-E14.5 (Rhinn et al, 2011;Sandell et al, 2012), and therefore T-Rex mutants contain significant amounts of functional RA, which were not detected by the reporter. Relevant to this discrepancy, the RA sensitivity assays aimed to calibrate the reporter (Cunningham et al, 2013) were carried out in vitro by whole embryo exposure to RA, a situation very different to in vivo RA delivery.…”
Section: Ra and Limb Developmentmentioning
confidence: 99%